The opposition in the second constitutional monarchy period: the case of Ahmet Samim - Hastaş, Mehmet T. (Thesis (M.A.)-Bogazici University. Atatürk Institute for Modern Turkish History, 2004., 2004)
Ahmet Samim was one of the three journalists assassinated after the declaration of the second constitutional monarchy. Samim, who was a fervent opponent of the Committee of Union and Progress, was also one of the founders of the Ahrar Fırkası (Liberal Party). This thesis analyses Samim's articles published in Sadayı Millet (Sound of the Nation), touching on the internal politics. Samim's articles are evaluated against a background describing the political atmosphere of the period. In this background we have chosen some subtitles: The amendments of 1909, the thought of Prince Sabahaddin, the elections of 1908 and the parliament, Grand Viziers and cabinets in the period of 1908-1910. Samim's articles are analysed in eight subdivisions: constitutional monarchy, the military service of non-Muslims, the union of the elements, the press, the revolt in Albania, the Committee of Union and Progress, Abdülhamit and the ancien regime, and the minister of public works, Hallacyan Efendi.In the conclusion, after summarising Samim's opinions, his position in the political atmosphere of the second constitutional monarchy is described.